(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:End stage renal diseases patients have lower seroconversion rates compared with the subjects with intact renal function. Moreover, even after the completion of vaccination schedule anti-hepatitis B titers of responder who kept on dialysis, patients are low and decline logarithmically with time. Objectives:To determine the response of patients with end stage renal disease undergone hemodialysis to hepatitis B virus vaccination and to identify the factors that could affect this response. Methods:One hundred patients with an age range from 21 to 75 years complaining of chronic renal failure on regular hemodialysis. Patients negative for hepatitis B antigen and anti-hepatitis C were vaccinated with 40µg of Euvax B intramuscularly in the deltoid muscle by following a schedule of 0, 1 and 2 months. The antibody titer was tested at third month and if titer was